Molecular and Immunological Study of Rotaviral Infection among Children in Anbar Governorate - Zainab Ahmed Ali; Noor N. Al-Hayani; Mohammed M. Moshrif (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Rotavirus infection is considered one of the most common causes of acute gastroenteritis in children less than 5 years and may be responsible for approximately 5% of all child deaths yearly. It is very contagious virus that causes diarrhoea in most babies and young children, vomiting and fever are also common. It is transmitted by fecal-oral contact and contaminated surfaces and hands also directly from person to person also. Aim of the Study: The current study aimed to study the role of rotaviral infection among all the clinically diagnosed children with watery diarrhoea, fever and vomiting detect by RT- PCR technique as a cut off molecular diagnosis tool in detection, evaluation the role of some immunological parameters in serum of rotaviral infected children act as mediators in immune response like the level of Interleukin-6 and Interferon gamma by ELISA technique. Patients and Methods: A total of (75) stool samples obtained from children <5 years with acute gastroenteritis were randomly collected from Maternity and Children at al-Anbar governorate from October 2019 January 2020. Rotavirus and Adenovirus was detected by rapid test for stool samples and Rotavirus, Norovirus and Astrovirus detect by real-time polymerase chain reaction . 5 ml of blood sample were also obtained to investigated the level of Interleukin-6 and Interferon gamma by ELISA technique. Result: Out of 75 enrolled in this study , rapid test rotavirus positive Ag was found in 75 (100%) and 28(37.3%) was adenovirus positive Ag (as mixed infection). RT-PCR were used for detection of viral genome from the total rotavirus result was 72(96.0%) as positive, 46(61.3%), Norovirus 29(38.7%) as positive result and Astrovirus 0.0(0.0%) as negative result. From 73 cases have positive rotavirus results, Interferon gamma recorded 31(43.1%) as positive results and 19(40.4%) as negative while IL-6 recorded 21(29.2%) as positive results and 51(70.8%) as negative result.